Pengaruh Dukungan Sosial Keluarga terhadap Kemampuan Bahasa Ekspresif Anak Autisme di Pusat Layanan Autis Yogyakarta - Hanindya Ayusti, Yemima; Muryanti, Muryanti; Jumiarti, Jumiarti (Jurnal Terapi Wicara dan Bahasa, 2023)
ABSTRACT Research Background: Family is the closest social environment that is owned by every human being. Social support is the perception and reality that an individual can get help from other people in his social network. Expressive language is the language children use to express their desires and to ask and answer questions. Children with autism disorder are children who have problems in aspects of language, one of them is expressive language. Goals: This research aims to determine whether family social support can affect the expressive language skills of children with autism at the Yogyakarta Autism Service Center. Methods: This research is a quantitative research with cross sectional research design. The sampling technique used a purposive sampling technique with a total sample of 30 autistic children at the Yogyakarta Autism Service Center. The data in this study were analyzed univariately and bivariately. The statistical test used is the Spearment Rank test. Research Result: The test results of bivariate analysis of family social support with expressive language skills of children with autism showed that ρ=0.000 with a correlation coefficient of r=0.628 it’s means that there is an influence between family social support and expressive language abilities of children with autism at the Yogyakarta Autism Service Center. The relationship between the two variables is included in the strong category with a positive direction. Conclusion: Family social support influences the expressive language skills of children with autism at the Yogyakarta Autism Service Center. Keywords: Family Social Support, Expressive Language Skills, Autism.